Green Credit, Corporate Social Responsibility and Company Value: Evidence From Indonesia and China Banks - Soares, Ersilda Dos Santos Mota; Pangestuti, Irene Rini Demi (Postgraduate Program Merdeka University, 2024)
The objective of this study is to investigate the influence of green credit and Corporate Social Responsibility (CSR) on company value, with profitability as a mediating factor, in banks in Indonesia and China from 2019 to 2022. This research uses a purposive sampling method in selecting the sample. The objects in this research are banks in Indonesia and China. Data analysis in this research uses multiple linear regression analysis. The findings reveal that green credit significantly affects profitability, whereas CSR does not. Neither green credit nor CSR directly impacts company value, but profitability as a mediating variable significantly influences company value. Indirectly, green credit through profitability significantly affects company value, while CSR does not. This research provides interesting contributions to stakeholders, related to green credit and sustainability programs. Therefore, this study can offer new insights. Limitations include the study's focus on a limited sample of banks that offer green credit and CSR, the restriction to four years of data without accounting for external factors like the COVID-19 pandemic, and the use of a single analytical tool. JEL Classification: G32; Q56; M14; L25 DOI: https://doi.org/10.26905/afr.v7i3.13019